2022
DOI: 10.3389/fncel.2022.923811
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Involvement in Cognitive Processes for New Therapeutic Considerations

Abstract: Cognitive impairment may be a consequence of the normal aging process, but it may also be the hallmark of various neurodegenerative and psychiatric diseases. Early identification of individuals at particular risk for cognitive decline is critical, as it is imperative to maintain a cognitive reserve in these neuropsychiatric entities. In recent years, galectin-3 (Gal-3), a member of the galectin family, has received considerable attention with respect to aspects of neuroinflammation and neurodegeneration. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 130 publications
1
6
0
Order By: Relevance
“…Anti-inflammatory factors secreted by M2-type microglia cells can reduce inflammation and improve ischemic brain injury. The neurotrophic factors secreted by it can promote the proliferation of neural precursor cells, accelerate the migration of neuroblasts ( 99 ), promote the maturation of new neurons, and promote the repair of the central nervous system. In addition, after ischemic stroke, M2-type microglia and macrophages, compared with M1 phenotypes, have a stronger phagocytosis capacity for necrotic neurons to remove damaged neurons, prevent secondary inflammatory reactions, and provide survival space for new neurons to maintain the homeostasis of the central nervous system under pathological conditions.…”
Section: Microglia Activation and Cns Disordersmentioning
confidence: 99%
“…Anti-inflammatory factors secreted by M2-type microglia cells can reduce inflammation and improve ischemic brain injury. The neurotrophic factors secreted by it can promote the proliferation of neural precursor cells, accelerate the migration of neuroblasts ( 99 ), promote the maturation of new neurons, and promote the repair of the central nervous system. In addition, after ischemic stroke, M2-type microglia and macrophages, compared with M1 phenotypes, have a stronger phagocytosis capacity for necrotic neurons to remove damaged neurons, prevent secondary inflammatory reactions, and provide survival space for new neurons to maintain the homeostasis of the central nervous system under pathological conditions.…”
Section: Microglia Activation and Cns Disordersmentioning
confidence: 99%
“…Future research exploiting mouse models with the neuron-specific deletion of Lifr will help delineate how LIF mediates brain responses to peripheral cancers. On the other hand, the precise identity of Gal3 receptor(s) is currently under debate, 40 42 rendering it a challenge to elucidate the molecular mechanism of Gal3 action on the brain. It is possible that Gal3 can function via its putative receptor(s) expressed by neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Another player of interest in the complex network of intercellular communication is GALECTIN, a β-galactosidase binding protein that is present in both the nucleus and cytoplasm. GALECTIN is involved in the control of phagocytosis and macropinocytosis ( 29 , 30 ). In summary, our study suggested that CD70 and GALECTIN may be potential biomarkers or targets for the diagnosis and treatment of HFRS.…”
Section: Discussionmentioning
confidence: 99%